Citrullus colocynthis (L.) Schrad (Bitter Apple Fruit): Promising Traditional Uses, Pharmacological Effects, Aspects, and Potential Applications - Li, Qin-Yuan; Munawar, Mahzaib; Saeed, Muhammad; Shen, Ji-Qiang; Khan, Muhammad Sajjad; Noreen, Sobia; Alagawany, Mahmoud; Naveed, Muhammad; Madni, Asadullah; Li, Chang-Xing (Frontiers in Pharmacology, 2022)
Health consciousness and increased knowledge about the side effects of synthetic drugs have enhanced interest in traditional medicines. Medicinal plants offer cures for various diseases, leading to improved living standards. This has brought ethnomedicinal studies into the spotlight and increased demand for herb-based medicines. Citrullus colocynthis is an herbaceous plant containing an abundance of nutrients that play a key role in the improvement of wellbeing. C. colocynthis has many biological properties, such as antioxidative, hypoglycemic, antibacterial, anti-cancerous, anti-inflammatory, analgesic, gastrointestinal tract, reproduction, protection, anti-microbial, antidiabetic, hypolipidemic, antineoplastic, profibrinolytic, anti-allergic, pesticidal, and immune-stimulatory. There are numerous bioactive compounds like cucurbitacin, flavonoids, and polyphenols in C. colocynthis that give it medicinal properties. Herein, we have extensively compiled, reviewed, and analyzed significant information on C. colocynthhis from the best published available evidence in PubMed, Scopus (Embase), Web of Science (Web of Knowledge), Cochrane Library, and Google Scholar, etc. Scientific literature evidenced that owing to the bioactive constituents, including cucurbitacin, polyphenols, flavonoids, and other potent molecules, C. colocynthis has many pharmacological and physiological functions. It possesses multi-beneficial applications in treating various disorders of humans and animals. So, the primary purpose of this comprehensive review is to provide an overview of the findings of positive impacts and risks of C. colocynthis consumption on human health, especially in poultry and veterinary fields. In the future, this narrative article will be aware of discoveries about the potential of this promising natural fruit and its bioactive compounds as the best nutraceuticals and therapeutic drugs in veterinary and human medicine.